Cellular stress induces cancer stem‐like cells through expression of DNAJB8 by activation of heat shock factor 1. Issue 3 (20th February 2018) - Kusumoto, Hiroki; Hirohashi, Yoshihiko; Nishizawa, Satoshi; Yamashita, Masamichi; Yasuda, Kazuyo; Murai, Aiko; Takaya, Akari; Mori, Takashi; Kubo, Terufumi; Nakatsugawa, Munehide; Kanaseki, Takayuki; Tsukahara, Tomohide; et al.
Abstract : In a previous study, we found that DNAJB8, a heat shock protein (HSP) 40 family member is expressed in kidney cancer stem‐like cells (CSC)/cancer‐initiating cells (CIC) and that it has a role in the maintenance of kidney CSC/CIC. Heat shock factor (HSF) 1 is a key transcription factor for responses to stress including heat shock, and it induces HSP family expression through activation by phosphorylation. In the present study, we therefore examined whether heat shock (HS) induces CSC/CIC. We treated the human kidney cancer cell line ACHN with HS, and found that HS increased side population (SP) cells. Western blot analysis and qRT‐PCR showed that HS increased the expression of DNAJB8 and SOX2. Gene knockdown experiments using siRNAs showed that the increase in SOX2 expression and SP cell ratio depends on DNAJB8 and that the increase in DNAJB8 and SOX2 depend on HSF1. Furthermore, treatment with a mammalian target of rapamycin (mTOR) inhibitor, temsirolimus, decreased the expression of DNAJB8 and SOX2 and the ratio of SP cells. Taken together, the results indicate that heat shock induces DNAJB8 by activation of HSF1 and induces cancer stem‐like cells. Abstract : Cancer stem cells are induced by cellular stress. Cellular stress activates HSF1 and induces DNAJB8, a cancer stem cell‐specific heat shock protein. HSF1/DNAJB8 is a novel pathway of cancer stem cells.